Гельмінтофауна бичків (Gobiidae) Одеської затоки Чорного моря - Квач, Ю.В. (Вестник зоологии, 2007)
У бычков в Одесском заливе обнаружено 10 видов гельминтов, среди которых наиболее распространенные: трематоды Cryptocotyle concavum (Creplin), C. lingua (Creplin), нематода Dichelyne minutus (Rudolphi) и акантоцефал Acanthocephaloides propinquus (Dujardin). Подтверждено существование в заливе пяти видов паразитов бычков, обнаружено 5 видов гельминтов. n total, 10 helminth species are found in gobiids of the Gulf of Odessa. The trematodes Cryptocotyle concavum (Creplin), C. lingua (Creplin), nematode Dichelyne minutus (Rudolphi) and acanthocephalan Acanthocephaloides propinquus (Dujardin) are the most widespread species. Five parasite species infecting gobiids are confirmed to exist in the Gulf. Also 5 helminth species are recorded for the first time in the Gulf of Odessa fauna.